Added prognostic value of cardiopulmonary test variables in low-risk pulmonary artery hypertension patients. (3rd October 2022) - Luna, R; Martinez Menaca, A; Otero Escudero, M; Segura De La Cal, T; Flox, A; Arribas Ynsaurriaga, F; Escribano Subias, P
Abstract: Background: Pulmonary artery hypertension (PAH) results in progressive right heart failure, functional decline and finally death or the need for a lung transplant. Prognostic assessment based on a 6-minutes walking test (6MWT) may be insufficient due to the possibility of a ceiling effect, especially in young patients. Purpose: To demonstrate the added prognostic value of functional assessment by cardiopulmonary exercise testing (CPET) in patients with a low-risk 6MWT. Methods: We conducted a retrospective cohort study in patients with PAH referred to two centres between June 2006 and December 2021, who met the following criteria: PAPm ≥25 mmHg, PCP≤15 mmHg, PVR >3 UW, age>18 years and had a CPET performed in the same week as the 6MWT. For CPET variables showing statistical significance, optimal cut-off points were determined. The kappa statistic was used to test interrater reliability between low-risk classification with CPET and the 6-minute test using the Kappa index. Finally, the added prognostic power of CPET variables was assessed in low-risk patients according to TM6D (defined as >440 metres) by survival analysis. Results: We included a total of 313 patients (27% male). 116 patients (64.8%) walked more than 440 metres at TM6D, this subgroup being significantly younger than those who walked less than 440 metres (42±11 vs 48±16 years) and with a higher proportion of men (34.8% vs 23.4%). In patients who walked more than 440 metres, we applied the CPET model associated with prognosis according to the optimal cut-off points obtained (Eq CO2 VT1 ≥41 and/or peak VO2 <15 ml/kg/min). Of the 116 patients classified as good prognosis by the 6MWT, 84 patients (72%) had altered CPET prognostic values. No substantial reliability was demonstrated between the low-risk classification by CPET and 6MWT (K<0.6 in all cases). Kaplan-Meier survival analysis showed that patients with had Eq CO2 VT1 ≥41 and peak VO2 <15 ml/kg/min had a worse prognosis at 5-year follow-up, despite walking more than 440m 6MWT (Figure 1). Conclusion: Young patients may have a good-prognosis 6MWT and, however, be at high-risk of adverse events. A combination of CPET variables has a good predictive value for survival in low-risk 6MWT patients. Performing a CPET is mandatory in these patients to adequately stratify risk. Funding Acknowledgement: Type of funding sources: None.